Correlations Between Preseason Functional Test Scores and Game Performance in Female Collegiate Volleyball Players - Jason Brumitt; Christopher Patterson; Robert Dudley; Eric Sorenson; Tyler Cuddeford; Heidi Cooke; Linda Froemming (International Journal of Sports Physical Therapy)
# Background